2021
DOI: 10.25248/reas.e8021.2021
|View full text |Cite
|
Sign up to set email alerts
|

Construção de um protocolo de restrição de movimento de coluna (RMC) vertebral: relato de experiência

Abstract: Objetivo: Descrever a elaboração de um protocolo de restrição de movimento de coluna (RMC) vertebral do Serviço de Atendimento Móvel de Urgência de Belo Horizonte. Relato da experiência: Trata-se de um relato de experiência sobre a construção de um protocolo de RMC vertebral. Foi realizada a busca na literatura das melhores evidências sobre o tema, seguida de análise crítica dos estudos e a construção de um fluxograma de decisão para indicação ou não de RMC vertebral. Ficou definido que a RMC vertebral será re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…With this in mind, it is possible to affirm that with the proper theoretical and practical training, nursing contributes to the qualification of care with SMR. This statement is supported by other studies that have identified that this measure prevents prolonged use of immobilization, avoids patient discomfort, and improves care flow in overcrowded emergency rooms [27][28] .…”
Section: Discussionsupporting
confidence: 65%
“…With this in mind, it is possible to affirm that with the proper theoretical and practical training, nursing contributes to the qualification of care with SMR. This statement is supported by other studies that have identified that this measure prevents prolonged use of immobilization, avoids patient discomfort, and improves care flow in overcrowded emergency rooms [27][28] .…”
Section: Discussionsupporting
confidence: 65%
“…Com isso, é possível afirmar que com a devida capacitação teórico-prática, a enfermagem contribui para a qualificação do cuidado em relação à RMC. Essa afirmação apoia-se em outras pesquisas que identificaram que essa medida previne o uso prolongado da imobilização, evita o desconforto dos pacientes e melhora o fluxo de atendimento em emergências superlotadas [27][28] .…”
Section: Discussionunclassified
“…Teniendo esto en cuenta, es posible afirmar que con la formación teórica y práctica adecuada, la enfermería contribuye a la cualificación de los cuidados en relación con la RMC. Esta afirmación está respaldada por otros estudios que han identificado que esta medida previene el uso prolongado de la inmovilización, evita molestias al paciente y mejora el flujo asistencial en las salas de urgencias saturadas [27][28] .…”
Section: Discussionunclassified